REFORMS OF PHYSICAL EDUCATION - BETWEEN ESSENCE AND EXISTENCE - Goran Šekeljić; Milovan Stamatović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2006)
We have analyzed the inefficiency of Physical Education Teaching.The reasons for this work are the latest changes of curriculum in the field of Physical and Health Education from the first up to the fourth grade of the elementary school and the estimation of the efects that are going to be produced in the teaching itself. The problems of teaching are, as we have already shown in the analyses, much more complicated and we do not believe that the reforms at the level of program contents are going to influence more significantly on the improvement of the efficiency and the achievements in pteaching of Physical and Health education